Molecular variation in population structure of Xanthomonas axonopodis pv Manihotis in the south eastern Nigeria - Ogunjobi, A.A.; Fagade, O.; Dixon, A. (2006)
Xanthomonas axonopodis pv manihotis (Xam) is the causal agent of cassava bacterial blight (CBB) in all cassava growing areas of the world. To develop an efficient disease management strategy, the genetic diversity of the pathogens population ought to be known. Information is scarce on the genetic diversity of Xam population in Nigeria. Random amplified polymorphic DNA (RAPD) was used to characterize Xam isolates from the southeastern parts of Nigeria. Seventeen Xam strains and two reference strains were analyzed with four RAPD primers. RAPD fragment data showed five major clusters at 80% similarity coefficient level. Four strains were not clustered by this analysis (Del5A, Imo38B, Ebon28A and Ebon27A) and were not grouped with the others in the dendrogram. Principal component analysis (PCA) assembly grouped the bacterial strains into three. One of the strains that was separated in the dendrogram was also clustered separately from the others in the major cluster in the PCA. The results showed a high level of genetic diversity in the pathogen.